Evolving challenges and strategies for fungal control in the food supply chain. (June 2021) - Davies, Catheryn R.; Wohlgemuth, Franziska; Young, Taran; Violet, Joseph; Dickinson, Matthew; Sanders, Jan-Willem; Vallieres, Cindy; Avery, Simon V.
Abstract: Fungi that spoil foods or infect crops can have major socioeconomic impacts, posing threats to food security. The strategies needed to manage these fungi are evolving, given the growing incidence of fungicide resistance, tightening regulations of chemicals use and market trends imposing new food-preservation challenges. For example, alternative methods for crop protection such as RNA-based fungicides, biocontrol, or stimulation of natural plant defences may lessen concerns like environmental toxicity of chemical fungicides. There is renewed focus on natural product preservatives and fungicides, which can bypass regulations for 'clean label' food products. These require investment to find effective, safe activities within complex mixtures such as plant extracts. Alternatively, physical measures may be one key for fungal control, such as polymer materials which passively resist attachment and colonization by fungi. Reducing or replacing traditional chlorine treatments ( e.g. of post-harvest produce) is desirable to limit formation of disinfection by-products. In addition, the current growth in lower sugar food products can alter metabolic routing of carbon utilization in spoilage yeasts, with implications for efficacy of food preservatives acting via metabolism. The use of preservative or fungicide combinations, while involving more than one chemical, can reduce total chemicals usage where these act synergistically. Such approaches might also help target different subpopulations within heteroresistant fungal populations. These approaches are discussed in the context of current challenges for food preservation, focussing on pre-harvest fungal control, fresh produce and stored food preservation. Several strategies show growing potential for mitigating or reversing the risks posed by fungi in the food supply chain.